PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE (LC) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVc SD NEGERI 169 PEKANBARU - Setiawan, Budi; Alpusari, Mahmud; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning science study class IVc SD Negeri 169 Pekanbaru. KKM achieved by school was 75. From 42 students who achieve KKM just 19 students (45.24%) while students who did’nt achieve KKM is 23 students (54.76%) with a class average of 66.90. The purpose of this research to improve learning outcomes IPA class IVc SD Negeri 169 Pekanbaru with the application of learning models Learning Cycle. The results obtained by the average value of 66.90 basic score increased in the first cycle of 3,39% to 69.17. In the second cycle the average value of students also increased by 14,42% to 76.55. On the basic of classical completeness score IPA student learning outcomes is only 45,24% (not finished). After the professor of applied learning model Learning Cycle (LC) in the first cycle classical completeness increased to 64,28% (not finished), and the second cycle of classical completeness obtained are increased to increase to 83,33%. Activities of teachers at the first meeting of first cycle acquire a percentage of 65% with enough categories. The second meeting increased to 70% in enough categories. In the first meeting of second cycle increased to 75% with good category. At the second meeting increased to 80% with good category. Activities of students in the first meeting of the first cycle acquire a percentage of 65% with enough categories. The second meeting increased to 70% in enough categories. In the first meeting of the second cycle increased to 75% with good category. At the second meeting increased to 80% with good category.Keywords : Learning Cycle, learning outcomes IPA